Investing in human capital to boost growth - Floro Ernesto Caroleo; Francesco Pastore (Institute of Labor Economics (IZA), 2017)
The Italian economy performs well below the EU average. The reason is a dramatic and persistent low rate of investment, always invoked but never supported by national and supra-national institutions. However, investment to increase the quantity and quality of human capital is key to boost economic growth and cannot be achieved without adequate financial resources. At the same time, the educational system needs to relaunch university reforms (including the Gelmini and 3+2 reforms) which have been unsuccessful so far because they were poorly implemented. Last but not least, more and better ties between the educational system and the labor market should be developed as soon as possible.
Keywords: E22; E24; H54; I25; I28; J24; 330; public investment; aggregate human capital; economic growth; educational reforms; 3+2 University Reform